The Antecedents of Economy-class Passenger Loyalty The Moderating Role of Airline Business Models: Full-service and Low-cost Airlines - Önder Kethüda; Emre Dil; Mehmet Akif Öncü (Istanbul Business Research)
In recent decades full-service airlines have targeted price-sensitive passengers, traditionally targeted by low-cost airlines, by promoting their economy class options. This paper aims to guide both types of airlines in promoting their economyclass options by utilizing factors influencing passenger preferences and loyalty. This paper identifies the relationship between the factors influencing economy-class passengers’ airline preferences and passenger loyalty. It also shows the moderating the role of the airline business models, i.e., full-service and low-cost, in this relationship. The data was collected at airports from 418 passengers who had just traveled or would soon travel. The results indicate that schedule convenience influences the airline choice of economy-class passengers the most. Furthermore, passenger loyalty is significantly influenced by in-flight experience, schedule convenience, and punctuality, but not by affordability, assurance, and booking experience. Additionally, the type of airline business model moderates the influence of affordability on passenger loyalty. Full-service and low-cost airlines targeting price-sensitive passengers with economy class options are recommended to ensure schedule convenience and punctuality.